A Case Study in Teaching: The Factors Determining of Assessmenting the Competence of Technology-Based - Phan, Thanh Chi; Phan, Tien Minh; Ngo, Thanh Tu; Duong, Ninh Toan Van (Review of Information Engineering and Applications, 2019)
Assessment and measurement of learning outcomes are an important part of the teaching process. In addition to supporting content learning, technology-based assessments are more advantageous than traditional assessments, as it can help reduce time as well as provide more access to student needs and preferences, allowing educators to personalize learning. Nowadays, more and more different types and assessment tools are applied to assess according to competence, helping teachers to get the most accurate, objective and reliable results about the learners' competencies. Advances in technology will extend the use of student competence assessments aimed at improving the efficiency of the learning process in education. The goal of competence-based education is to focus on the output of the teaching and learning process, which emphasizes the competence and level of competence that learners need to achieve after the end of a training program, thus the development of technology, technology, socio-economy and politics from education has been identified as a key task in teaching towards developing competence for learners. This paper researches and identifies the factors in competence-based assessment with technology-assisted, contributing to identifying ways of assessing learners in the direction of competence development, aiming to diversify methods of student assessment in teaching and online teaching.